Investigação do nível de proximidade da natureza dos educandos das escolas situadas na zona de amortecimento do Parque Natural Municipal dos Morros em Santa Maria - RS - Santos, Lucas Mauricio Willecker dos (2022)
In order to control the impacts caused by societies the Protected Areas are created, as areas that are instituted by the need to protect certain priority territorial spaces for conservation, with the intention of promoting a healthier society and a balanced environment by managing the use of natural resources in a broader and more democratic manner (BENSUSAN, 2006). To this end, Brazil has created Conservation Units (UCs) that have different categories, at the federal, state, and municipal levels. One of the types of UCs belonging to the category of full protection are the National Parks. The parks seek to preserve natural ecosystems of great ecological relevance and scenic beauty, enabling scientific research and the development of environmental education and interpretation activities, recreation in contact with nature and ecological tourism (BRASIL, 2000). Given the above, the Municipal Natural Park of the Hills arises in the municipality of Santa Maria as an attempt to preserve the forest remnants of the Atlantic Forest Biome present in the urban area of the municipality, in addition to water resources and scenic beauty of the site, thus enabling recreation and contact with nature, contemplation of the city of Santa Maria and the development of educational activities, scientific research and environmental interpretation. Based on this, the present research sought to value the proximity to nature of seventh grade students of schools in the Buffer Zone of the Municipal Natural Park of Morros through the analysis of perception. To this end, the research methodology relied on the application of a photo-test using the Likert (1932) school of evaluation in which the students attributed grades as to the proximity of images of the city of Santa Maria presented. From then on, the results pointed out that there is a distancing of the students in relation to images related to nature captured within the UC. Therefore, an instrument was designed to synthesize some information about the Parque Natural Municipal dos Morros to be sent to the schools that participated in the photo-test. The research included the preparation of a booklet containing information to help teachers and students, especially in the seventh grade of elementary school, which, according to the BNCC (2017), aims to learn about and work with the municipal CUs. Despite being inserted primarily in the contents of the seventh grade, the material is presented in a playful and objective way so that it can be understood by different audiences as well, aiming to seek the support and knowledge of the surrounding population for the preservation and conservation of the Parque dos Morros in the municipality.